A lifelong study of a pack Rhodesian ridgeback dogs reveals subclinical and clinical tick-borne Anaplasma phagocytophilum infections with possible reinfection or persistence - Hovius, Emil; de Bruin, Arnout; Schouls, Leo; Hovius, Joppe; Dekker, Niels; Sprong, Hein (Parasites & vectors, 2018)
Background Various tick-borne infections often occur without specific clinical signs and are therefore notoriously hard to diagnose separately in veterinary practice. Longitudinal studies over multiple tick seasons performing clinical, serological and molecular investigations in parallel, may elucidate the relationship between infection and disease. In this regard, six related Rhodesian Ridgeback dogs living as a pack became subject of lifetime studies due to ongoing tick infestations and recurring clinical problems. Blood samples for diagnostic tests were obtained throughout the years 2000 to 2009. Methods Data collected from clinical observations , hemograms, serology and detection of Anaplasma phagocytophilum , either by microscopy or by DNA amplification and typing, were placed in a time line. This dataset essentially presents as a prospective study enabling the association of the Anaplasma infections with occurring disease. Results All six dogs were infected, and two of them developed particular clinical symptoms that could be associated with Anaplasma infections over time. More specifically, episodes of general malaise with fever and purpura with thrombocytopenia and bacterial inclusions in granulocytes, were found concurrently with Anaplasma DNA and specific antibodies in peripheral blood samples. DNA from A. phagocytophilum variant 4 (of 16S rRNA) was found in multiple and sequential samples. DNA-sequences from variant 1 and the human granulocytic ehrlichiosis (HGE) agent were also detected. Conclusions In this study two lifelong cases of canine anaplasmosis (CGA) are presented. The data show that dogs can be naturally infected concurrently with A. phagocytophilum variant 1, variant 4 and the HGE agent. The ongoing presence of specific antibodies and Anaplasma DNA in one dog indicates one year of persisting infection. Treatment with doxycycline during recurring clinical episodes in the other dog resulted in transient clinical improvement and subsequent disappearance of specific antibodies and DNA suggesting that re-infection occurred.